ბიზანტიელ ქალთა სახეები კონსტანტინოს კავაფისის ლექსების - „ანა კომნენეს“ და „ანა დალასინის“ - მიხედვით - გამრეკელი, თეა (ლოგოსი, 2022)
Much of the poetry of the Modern Greek poet Constantine Cavafy deals with Byzantium, the Byzantine emperors, and Byzantine culture. Cavafy’s interest in Byzantium is evident early in his poetic career and manifests itself throughout his poetry. This interest was partly due to Cavafy's origins: The Alexandrian-born poet, who lived over two years in Constantinople, his mother's hometown, considered himself as the heir of the Byzantine world. Cavafy, as he himself claimed, was a ‘poet-historian.’ He composed poems and wrote history. Cavafy divided his historical and pseudo-historical poems into thematic categories. He grouped the poems on Byzantium and called the collection ‘Byzantine Days.’ The Alexandrian poet took a special interest in the Komnenos dynasty. This paper deals with two famous Byzantine female figures - Anna Komnene and Anna Dalassene, Alexios I Komnenos’ family members. In the paper, we will discuss the poems Anna Komnene and Anna Dalassene which Cavafy created based on the same historical source Alexiad, and see what is important and noteworthy to Cavafy, both as a historian and as a poet, how he uses historical information in his poems, how he expresses his poetic utterance based on that information, and how he creates the portraits of famous Byzantine women.